Campaigns of knowledge U.S. pedagogies of colonialism and occupation in the Philippines and Japan - Schueller, Malini Johar 1957- (Quezon City Ateneo de Manila University Press, 2021)
The creation of a new school system in the Philippines in 1898 and educational reforms in occupied Japan, both with stated goals of democratization, speaks to a singular vision of America as savior, following its politics of violence with benevolent recuperation. The
pedagogy of recovery—in which schooling was central and natives were forced to accept empire through education—might have shown how Americans could be good occupiers, but it also created projects of Orientalist racial management: Filipinos had to be educated and civilized, while the Japanese had to be reeducated and “de-civilized.”

In Campaigns of Knowledge, Malini Schueller contrapuntally reads state-sanctioned proclamations, educational agendas, and school textbooks alongside political cartoons, novels, short stories, and films by Filipino and Filipino Americans, Japanese and Japanese Americans to demonstrate how the U.S. tutelary project was rerouted, appropriated, reinterpreted, and resisted. In doing so, she highlights how schooling was conceived as a process of subjectification, creating particular modes of thought, behaviors, aspirations, and desires that
would render the natives docile subjects amenable to American-style colonialism in the Philippines and occupation in Japan.-- Back cover.
Originally published by Temple University
Originally published
Keywords: Educational change -- Japan -- History -- 20th century; Educational change -- Philippines -- History -- 20th century; Education -- Philippines -- American influences -- History -- 20th century; Education -- Japan -- American influences -- History -- 20th century; Philippines -- History -- 1898-1946.; Japan -- History -- Allied occupation, 1945-1952.